The great ice age - Maynard, Christopher (New York : Random House, 1987)
Briefly discusses the effects of the Great Ice Age on the earth's land formation, vegetation, and animals.
Includes index
Keywords: Glacial epoch-Juvenile literature; Glacial epoch